Praktik Sewa Menyewa Sawah Perspektif Ekonomi Islam - Diah - Mustika; Ficha - Melina (ISLAMIC BUSINESS and FINANCE, 2022)
AbstractRenting is a form of muamalah that many people do to meet their needs. For rural communities who work as farmers, leasing is done with objects in the form of rice fields. Leasing in practice must be by applicable Islamic rules. The purpose of this study is to find out how the practice of leasing rice fields and the view of Islamic Economics. This type of research is field research. Researchers conducted interviews with 10 informants. Based on the results of research on the practice of leasing rice fields in Kampung Kemuning Muda, it is carried out directly between the tenants of the fields and the owners of the fields, the agreement is made by deliberation and the contract is verbal, the rental agreement transaction is carried out at the beginning of the contract by determining the payment of rent and the rental period. At the same time, there were no witnesses who witnessed the agreement. The practice of leasing rice fields according to an Islamic economic perspective is legal and fulfills the pillars and conditions of ijarah. The owner of the rice field has earned wages from the field that is leased, then the tenant of the field benefits from planting the rice that has been rented. As well as relating to the harvest obtained each season can improve the economy of the community.Keywords: Islamic Economics, Practice, Leasing